Chaos Of Double Diffusive Convection In The Presence Of Feedback Control Strategy - Zailan Siri,; Siti Norfarahin Hasan,; Rose Irnawaty Ibrahim (International Academy Publishing (IAP), 2024)
Non-Indexed Publication